Orations of the Fatimid caliphs : festival sermons of the Ismaili imams : an edition of the Arabic texts and English translation of Fatimid khuṭbas /: festival sermons of the Ismaili imams : an edition of the Arabic texts and English translation of Fatimid khuṭbas. (2009) - Unknown
No abstract available